Comprehensive Assessment of Somatostatin Receptors in Various Neoplasms: A Systematic Review - Shista Priyadarshini; Derek B. Allison; Aman Chauhan (Pharmaceutics, 2022)
Somatostatin receptors (SSTR) are expressed in various neoplasms and can be targeted for both diagnostics as well as therapeutics. This systematic review aims to compile and discuss the prevalence of somatostatin receptor expression in various neoplasms. We performed a literature search from Google Scholar and PubMed using relevant keywords to look for all publicly available data regarding SSTR expression in various cancers. Both histopathological and radiographical studies were included for SSTR assessment. We found that many cancers express SSTR with varying prevalence. SSTR is now a well-established theranostics biomarker. We now have highly sensitive and specific diagnostic modalities like gallium 68 DOTATATE and copper 64 DOTATATE scans to screen for SSTR-2 and then target it therapeutically with lutetium 177 DOTATATE. A thorough understanding of SSTR expression in other tumors will open the channels for exploring potential SSTR targeting.